Idiopathic musculoskeletal pain, musculoskeletal pain syndromes, and use of electronic devices in adolescents with asthma - Mariana Machado Forti Nastri; Benito Lourenço; Ligia Bruni Queiroz; Luiz Eduardo Vargas da Silva; Daniela Mencaroni Rodrigues Lourenço; Ana Paula Beltran Moschione Castro; Clovis Artur Silva; Antonio Carlos Pastorino (Elsevier, 2022)
Objective: To evaluate idiopathic musculoskeletal pain, musculoskeletal pain syndromes, and use of electronic devices in adolescents with asthma and healthy controls. Methods: Cross-sectional study was conducted on 150 asthmatic adolescents and 300 controls. Adolescents completed a self-administered questionnaire regarding painful symptoms, use of electronic devices, and physical activity. Seven musculoskeletal pain syndromes were evaluated, and Asthma Control Test (ACT) was assessed. Results: Musculoskeletal pain (42% vs. 61%, p = 0.0002) and musculoskeletal pain syndromes (2.7% vs. 15.7%, p = 0.0006) were significantly lower in asthmatic adolescents than in controls. The frequency of pain in the hands and wrists was reduced in asthmatic than in controls (12.6% vs. 31.1%, p = 0.004), in addition to cell phone use (80% vs. 93%, p < 0.0001), simultaneous use of at least two electronic media (47% vs. 91%, p < 0.0001), myofascial syndrome (0% vs. 7.1%, p = 0.043), and tendinitis (0% vs. 9.2%, p = 0.008). Logistic regression analysis, including asthma with musculoskeletal pain as the dependent variable, and female sex, ACT > 20, simultaneous use of at least two electronic devices, cell phone use, and weekends and weekdays of cell phone use, as independent variables, showed that female sex (odds ratio [OR], 2.06; 95% confidence interval [CI], 1.929-6.316; p = 0.0009) and ACT ≥ 20 (OR, 0.194; 95% CI, 0.039-0.967; p = 0.045) were associated with asthma and musculoskeletal pain (Nagelkerke R2 = 0.206). Conclusions: Musculoskeletal pain and musculoskeletal pain syndromes were lower in adolescents with asthma. Female sex was associated with musculoskeletal pain in asthmatic, whereas patients with asthma symptoms and well-controlled disease reported a lower prevalence of musculoskeletal pain.